Silicon dioxide mask by plasma enhanced atomic layer deposition in focused ion beam lithography. (20th January 2017) - Liu, Zhengjun; Shah, Ali; Alasaarela, Tapani; Chekurov, Nikolai; Savin, Hele; Tittonen, Ilkka
Abstract: In this work, focused ion beam (FIB) lithography was developed for plasma enhanced atomic layer deposited (PEALD) silicon dioxide SiO2 hard mask. The PEALD process greatly decreases the deposition temperature of the SiO2 hard mask. FIB Ga + ion implantation on the deposited SiO2 layer increases the wet etch resistivity of the irradiated region. A programmed exposure in FIB followed by development in a wet etchant enables the precisely defined nanoscale patterning. The combination of FIB exposure parameters and the development time provides greater freedom for optimization. The developed process provides high pattern dimension accuracy over the tested range of 90–210 nm. Utilizing the SiO2 mask developed in this work, silicon nanopillars with 40 nm diameter were successfully fabricated with cryogenic deep reactive ion etching and the aspect ratio reached 16:1. The fabricated mask is suitable for sub-100 nm high aspect ratio silicon structure fabrication.